Monitoring and maintaining quality in the paediatric haemodialysis unit. - Uthup, Susan; Balan, Satish; Lobo, Valentine (Pediatric Nephrology, 2025)
Chronic kidney disease in children is being increasingly recognised and reported worldwide, and the focus of paediatric dialysis planning has changed from acute care alone to encompass chronic care. In many parts of the world, haemodialysis for children is performed in adult units and is based on standards established for adults. This review proposes standards for paediatric haemodialysis, incorporating special requirements for children while simultaneously drawing from the adult experience. We discuss the optimum requirements, including space utilisation, equipment needed, water treatment facilities, disposables, safety standards, staffing needs, monitoring and maintenance, infection prevention, waste disposal and quality indicators. We also review recent advancements in the field that should be incorporated into future dialysis units and the steps required for achieving carbon neutrality and protecting the environment.